Pengaruh Kualitas Pelayanan Terhadap Word of Mouth Melalui Kepuasan Orang Tua Sebagai Variabel Intervening Pada Kidsstar Preschool di Kota Makassar - Utama, Imelda; Karnawati, Tin Agustina; Handarini, Dany Moenindyah (Jurnal Pendidikan Indonesia, 2024)
Several problems arise in PAUD institutions along with their development, one of which is related to the lack of quality of PAUD services, which of course can cause dissatisfaction of parents and will have a negative impact on parents’ perceptions and ultimately can affect the resulting WOM. This study used Proportional Stratified Sampling technique. The instrument took questionnaires on 58 respondents of parents of students who were registered as active students until the May 2024 period, including 19 parents of Play Group class level, 17 parents of Kindergarten A class level and 22 parents of Kindergarten B class level. Quantitatively processed research data with path analysis techniques using Smart PLS 4.1.0.4 software. The results of this study are supported by primary data using a questionnaire. The analysis of this study shows that: (1) Service quality has a positive and significant effect on word of mouth, where the higher the Service Quality, the higher the Word of Mouth (2) Parental satisfaction has a positive and significant effect on Word of Mouth, where the higher the Parental Satisfaction, the higher the Word of Mouth. (3) Service quality has a positive and significant effect on Parental Satisfaction where the higher the Service Quality, the higher the Parental Satisfaction. (4) Service quality has a positive and significant effect on word of mouth through Parent Satisfaction.